Association Between Medicare Program Type and Health Care Access, Acute Care Utilization, and Affordability Among Adults With Cardiovascular Disease. Issue 9 (2nd September 2022) - Oseran, Andrew S.; Sun, Tianyu; Aggarwal, Rahul; Kyalwazi, Ashley; Yeh, Robert W.; Wadhera, Rishi K.
Abstract : Background: Medicare Advantage plans now provide health insurance coverage to >24 million older adults in the United States, and enrollment is increasing among individuals with cardiovascular disease (CVD). Whether Medicare Advantage enrollment is associated with similar health care access, acute care utilization, and financial strain for adults with CVD compared with traditional Medicare is unknown. Methods: We performed a cross-sectional study of Medicare beneficiaries 65 years or older with CVD using the 2019 National Health Interview Survey. We fit multivariable logistic regression models to examine the association of Medicare program type (Medicare Advantage versus traditional Medicare) with measures of health care access, acute care utilization, and affordability. Results: The weighted population included 11 013 437 Medicare beneficiaries, of whom 3 922 104 (35.6%) were enrolled in Medicare Advantage, and 7 091 334 (64.4%) were enrolled in traditional Medicare. Medicare Advantage and traditional Medicare enrollees were similar with respect to age, sex, racial/ethnic distribution, and household income; however, Medicare Advantage beneficiaries were more likely to live in an urban setting (82.7% versus 76.0%; P =0.01) and to be college educated (24.2% versus 19.0%; P =0.01). Medicare Advantage beneficiaries were more likely to have a usual source of care (93.5% versus 88.9%; OR, 1.99 [95% CI, 1.33–2.98)]; however, there were no other differences in health care access or utilization. Medicare Advantage beneficiaries were more likely to have problems paying medical bills (16.5% versus 11.6%; OR, 1.68 [1.17–2.40]) and to worry about paying medical bills (40.1% versus 33.8%; OR, 1.37 [1.07–1.76]) compared with those enrolled in traditional Medicare. Conclusions: Adults with CVD in Medicare Advantage were more likely to experience financial strain related to their medical bills compared with those in traditional Medicare. As enrollment in Medicare Advantage grows, policy efforts should focus on ensuring care is affordable for patients with CVD.